DETERMINATION OF POLYCYCLIC AROMATIC HYDROCARBONS IN SOIL AT AL-NAHRAWAN BRICKS FACTORY - Thamera K. M. Al-Rudaini and Israa M.H. Almousawi (Pakistan Journal of Biotechnology, 2018)
The concentration of sixteen polycyclic aromatic hydrocarbons were determined in soil samples at AL-nahrawan bricks factory. The measured period was two seasons' summer and winter. The soil samples collected from surface and depth chosen site and analyzed by GC apparatus. The most abundant compounds in the summer season were naphthalene, acenaphthene, fluorene, pyrene and benzo [a] anthracene, while in the winter were naphthalene, acenaphthene, fluorine, benzo [k] fluoranthene, benzo [a] pyrene. The concentrations of 16 PAH in the summer were higher than in the winter season.